Literature Review Red Ocean Strategy (Global Journal of Management and Business Research, 2023)
The term ocean strategy as introduced by the authors Renee Mauborgne W Chan Kim of the very famous research paper as well as book published Blue ocean strategy 1 where the term ocean means market and the strategy in reference of being blue focuses on creating a very new segment which is yet to be developed as a full fledge market and termed the other industrial strategies to be as red ocean strategies Excessive exploitation of existing demands by making a better offer to customers with a view to beat competition is termed as red ocean strategy 1 The authors mentioned that there are six common managerial beliefs as how to overcome competition in the business which they referred where false interpretations and named as red ocean traps The article investigates the existence of red ocean strategy
Keywords: red ocean strategy; red ocean traps; blue ocean strategy; competitive strategy